INDONESIAN EMPLOYMENT INSURANCE: A POLICY REVIEW - imran syuaib; Martin Lumeo Harima; Tranc Dinh Puon; Aida Fitriani; Markotib Markotib (Khairun Law Journal, 2022)
Insurance is considered a very useful form of defense, and can avoid risks in carrying out work or other activities. During activities, of course, there are risks and dangers that can occur, such as the risk of dismissal, work accidents, disability and even deathRisk is uncertainty in an ongoing activity (whether it is work or something outside of work). Another definition of risk is loss or the possibility of loss. Risk is divided into three parts, namely: financial risk, operational risk, and pure risk. To cover risk, an insurance is important and neede